Methodology for Structural and Parametric Optimization of Cascade Automatic Control Systems Based on Modified Smith Predictor - G. T. Kulakov; A. T. Kulakov; V. V. Kravchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper presents methodology for structural and parametric optimization of cascade ACS   technological parameters of thermal power processes which has been developed on the basis of a modified Smith predictor. The given methodology permits significantly to improve quality of regulation in comparison with the typical cascade AСS.